jarabhuiyan wrote:

16. The given equation is l

m+ n

= m

n + l

= n

l + m

= k . Forming the three equations yields l = (m + n)k, m =

(n + l)k, n = (l + m)k. Summing these three equations yields

l + m + n = (m + n)k + (n + l)k + (l + m)k

= k[(m + n) + (n + l) + (l + m)]

= k(m + n + n + l + l + m)

= k(2m + 2n + 2l)

= 2k(m + n + l)

1 = 2k by canceling m + n + l from each side

1/2 = k

Hence, Column A equals 1/2. Since 1/2 is greater than 1/3, Column A is greater than Column B, and the

answer is (A).

You, are incredible!! Thanks!! This opened up my eyes to a whole new way of problem solving!!!